Digital literacy: The catalyst for credit access and income growth in rural households - Ying Zhang; Haozhao Zhen; Yi Wang (PLoS ONE, 2026)
To clarify the role of digital literacy improvement in farm household income growth, this paper constructs a digital literacy assessment framework covering seven dimensions and uses data from a 2023 rural survey in China to empirically examine the impact of digital literacy on farm household income. The findings indicate that digital literacy significantly enhances income growth among farm households. Mechanism analysis reveals that digital literacy improves access to credit for farm households, thereby facilitating income growth. The effect of digital literacy on household income varies by group, with the highest marginal contribution to agricultural income among low-income households and to non-agricultural income among middle to high-income households. Digital literacy positively affects income across different genders and educational levels. The findings of this study reveal that digital literacy promotes income growth among different groups of rural households in China through various pathways.